SF-6D health state utilities for lifestyle, sociodemographic and clinical characteristics of a large international cohort of people with multiple sclerosis - Campbell, Julie A.; Jelinek, George A.; Weiland, Tracey J.; Nag, Nupur; Neate, Sandra L.; Palmer, Andrew J.; Mulhern, Brendan; De Livera, Alysha; Simpson-Yap, Steve (Quality of life research, 2020)
Background While many studies have examined the impacts of multiple sclerosis (MS) on health-related quality of life (HRQoL), none have used the SF-6D multi-attribute utility instrument in a large international cohort (> 2000 subjects) of people with MS. Objectives To derive SF-6D health state utilities (HSUs) for participants of the HOLISM (Health Outcomes and Lifestyle In a Sample of people with Multiple Sclerosis) international cohort and to describe the distribution and determinants thereof. Methods HSUs were generated using the SF-6D for participants with sufficient SF-36 data [ n = 2185/2466 (88.6%)]. Mean HSUs for sociodemographic, clinical and modifiable lifestyle factors (including diet, physical activity, supplement use) were evaluated. Determinants of HSU were then evaluated by linear regression, adjusted for age, sex, MS type, disability, fatigue, and prescription antidepressant use. Results Mean HSU for the sample was 0.67 (SD = 0.13) and diminished with increasing MS-related disability, robust to adjustment, supporting the SF-6D’s discriminatory power in people with MS. Severe disability and clinically significant fatigue were each associated with 11% lower HSU (95% CI = − 0.13, − 0.10 and − 0.12, − 0.10), and depression risk with 10%-lower HSU (95% CI = − 0.11, − 0.08). Employment, higher socioeconomic and married/partnered statuses, larger social-network size, greater physical activity, and vitamin D and omega-3 supplement use were associated with significantly higher HSU, and overweight/obese BMI and tobacco smoking with lower HSU. Age, sex, and education were not associated. Conclusion Modifiable lifestyle factors including healthy diet, increased physical activity and supplement use were associated with higher HRQOL among people with MS. The SF-6D instrument revealed significant discriminatory power in this international cohort of people with MS.